Lean Management Practices as a Driving Force for Guiding Administrative Leadership in Entrepreneurial Organizations: an Applied Study in Private Universities in The Middle Euphrates Region - Dunya Khammat Nashmi Al-Khuzaie; Ameera Ghasi Ajel; Estabraq Ali Kareem (International Journal on Economics, Finance and Sustainable Development, 2026)
The current study aims to identify the role of lean management practices across its dimensions (workplace organization, continuous improvement, multi-functional workers, and six-dimensional diffractometers) in enhancing entrepreneurial organizations in their dimensions (independence, creativity, proactivity, and risk tolerance). Accordingly, a sample of administrative leaders from private universities in the Middle Euphrates region was selected. (85) questionnaires were distributed to the study sample, and (81) valid questionnaires were retrieved for analysis. This necessitated clarifying the tools used to present the study's findings. The most important statistical tools used for this purpose were the structural modeling equation, Cronbach's alpha coefficient, arithmetic mean, standard deviation, Pearson's correlation coefficient, and regression coefficients, which were extracted using SPSS.V.29 and AMOS.V.29. Based on the results obtained by the study, it was found that there is a significant correlation and influence between the impact of lean management practices on organizations. Entrepreneurship. Perhaps the most important conclusion reached by the study was that applying lean management principles contributes significantly to enhancing the innovative capabilities of academic institutions, supporting a more flexible and innovative environment for knowledge production and teamwork.